BASICS OF SELF-ORGANIZATIONAL CULTURE FORMATION IN FUTURE SOCIAL TEACHERS - Kosshygulova, Aliya; KHASSANOVA, Saltanat; KOLUMBAYEVA, Sholpan (Pedagogy and Psychology, 2025)
Modern society’s requirements for university graduates include not only the ability to work in their professional field, but also the readiness for continuous learning, innovation and active work. That’s why, in the pedagogical process of a university, it is becoming increasingly important to manage the process of developing students’ self-organization skills. In order to solve the problem of forming an individual’s ability to self-organize requires understanding the education as the most important function of culture, as a “mechanism for launching new forms of culture”, “expanded reproduction and transmission of culture” (Abibulayeva, 2021). In this study, we strive to ensure the comprehensive development of future specialists, including the development of their ability to self-government, self-regulation and the choice of a culturally appropriate lifestyle. Based on the analysis, we can prove that the culture of self-organization formed in the educational process is a key element of successful professional development, creative self-development and achievement of personal growth.